Effects on and transfer across the blood-brain barrier in vitro—Comparison of organic and inorganic mercury species. Issue 1 (December 2016) - Lohren, Hanna; Bornhorst, Julia; Fitkau, Romy; Pohl, Gabriele; Galla, Hans-Joachim; Schwerdtle, Tanja
Abstract Background Transport of methylmercury (MeHg) across the blood-brain barrier towards the brain side is well discussed in literature, while ethylmercury (EtHg) and inorganic mercury are not adequately characterized regarding their entry into the brain. Studies investigating a possible efflux out of the brain are not described to our knowledge. Methods This study compares, for the first time, effects of organic methylmercury chloride (MeHgCl), EtHg-containing thiomersal and inorganic Hg chloride (HgCl2 ) on as well as their transfer across a primary porcine in vitro model of the blood-brain barrier. Results With respect to the barrier integrity, the barrier model exhibited a much higher sensitivity towards HgCl2 following basolateral incubation (brain-facing side) as compared to apical application (blood-facing side). These HgCl2 induced effects on the barrier integrity after brain side incubation are comparable to that of the organic species, although MeHgCl and thiomersal exerted much higher cytotoxic effects in the barrier building cells. Hg transfer rates following exposure to organic species in both directions argue for diffusion as transfer mechanism. Inorganic Hg application surprisingly resulted in a Hg transfer out of the brain-facing compartment. Conclusions In case of MeHgCl and thiomersal incubation, mercury crossed the barrier in both directions, with a slight accumulation in the basolateral, brain-facing compartment, after simultaneous incubation in both compartments. For HgCl2, our data provide first evidence that the blood-brain barrier transfers mercury out of the brain.